New Directions in the History of the Jews in the Polish Lands - Polonsky, Antony; Węgrzynek, Hanna; Żbikowski, Andrzej (Jews of Poland, 2018)
This volume is made up of essays first presented as papers at the conference held in May 2015 at POLIN Museum of the History of Polish Jews in Warsaw. It is divided into two sections. The first deals with museological questions-the voices of the curators, comments on the POLIN museum exhibitions and projects, and discussions on Jewish museums and education. The second examines the current state of the historiography of the Jews on the Polish lands from the first Jewish settlement to the present day.Making use of the leading scholars in the field from Poland, Eastern and Western Europe, North America, and Israel, the volume provides a definitive overview of the history and culture of one of the most important communities in the long history of the Jewish people.